Study of a rare medicinal plant Artemisia nilagirica: phytochemical screening, antioxidant properties and antimicrobial activities - Nayeema, Mehbubun (BRAC University, 2018)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2017.